Improving Mathematics Learning Outcomes Through The Problem Based Learning (PBL) Learning Model For Grade 4 Elementary School Students - Mughofir, Muh (Universitas Sebelas Maret, 2022)
This research aims to improve the mathematics learning outcomes of grade 4 students at SD Negeri 2 Demangan. This research is classroom action research which was carried out in two cycles and each cycle had three meetings. The subjects in this research were 25 grade 4 students at SD Negeri 2 Demangan. Data collection techniques use test techniques. The data analysis technique uses comparative descriptive in the form of a percentage of mathematics learning outcomes between pre-cycle and after the cycle. Based on the research results, it can be concluded that learning using the Problem Based Learning model can improve learning outcomes in mathematics subjects with flat shapes. The results before the action was taken were that in the pre-cycle only 11 students or 44% had completed it, in the first cycle it had increased to 16 students or 64% who had completed studying mathematics and in the second cycle it had increased again to 22 students who had completed studying mathematics or 88%. This research was said to be successful because it achieved a performance indicator of ≥ 80% of all students with a KKM ≥ 70.